2020
DOI: 10.3390/molecules25040901
|View full text |Cite
|
Sign up to set email alerts
|

Moscatilin Induces Apoptosis in Human Head and Neck Squamous Cell Carcinoma Cells via JNK Signaling Pathway

Abstract: Dendrobii Herba is an herbal medicine that uses the stems of Dendrobium species (Orchidacea). It has been traditionally used to treat fever, hydrodipsomania, stomach disorders, and amyotrophia. In our previous study, a bibenzyl compound, moscatilin, which is isolated from Dendrobii Herba, showed potent cytotoxicity against a FaDu human pharyngeal squamous carcinoma cell line. Prompted by this finding, we performed additional studies in FaDu cells to investigate the mechanism of action. Moscatilin induced FaDu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Apoptosis triggered by the caspase dependent pathway can be started off the extrinsic pathway or the intrinsic pathway (mitochondrial pathway). The extrinsic pathway leads to activation of caspase‐8 28 . As shown in Figure 1D, caspase‐8 increased obviously in NSCLC cells with mangiferin.…”
Section: Resultsmentioning
confidence: 85%
“…Apoptosis triggered by the caspase dependent pathway can be started off the extrinsic pathway or the intrinsic pathway (mitochondrial pathway). The extrinsic pathway leads to activation of caspase‐8 28 . As shown in Figure 1D, caspase‐8 increased obviously in NSCLC cells with mangiferin.…”
Section: Resultsmentioning
confidence: 85%
“…In conclusion, the chemical compositions of Dendrobii Herba, D. nobile, D. chrysanthum, and their hybrid, D. nobile × candidum, were analyzed via UPLC-QToF MS and were identified by comparing the ESI QToF MS data of the isolates (1-13) from Dendrobii Herba and the standards (14)(15)(16)(17). The results showed that the chemical compositions of each sample were different, demonstrating that each sample from different species could be well-distinguished, and the quality of the different samples could be determined through this method.…”
Section: Discussionmentioning
confidence: 99%
“…The methanol extracts of Dendrobii Herba, D. nobile, D. candidum, the hybrid, D. nobile × candidum, and compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) were analyzed using a Waters ACQUITY UPLC I-Class system combined with a Vion IMS QToF mass spectrometer (Waters). Each sample (1000 ppm, 2 µL) was injected into an ACQUITY UPLC BEH C18 column (2.1 mm × 100 mm i.d., 1.7 µm; Waters).…”
Section: Uplc-qtof Ms Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…At the molecular level, THM compounds seem to regulate tumorous properties through modulation of different external and intrinsic apoptotic signaling pathways. For instance, berberine, demethoxycurcumin, ursolic acid, tanshinones, oridonin, moscatilin and wogonin were all capable of suppressing oncogenic PI3K/Akt/mTOR and MAPK/JNK/p38 pathways thereby resulting in cell proliferation inhibition in HNSCC as well as in nasopharyngeal carcinoma [13,[22][23][24][25][26][27][28]. Moreover, mitochondrial-associated apoptotic regulators BCL-2 and Bax were also important mediators for THM-related antigrowth/survival activity.…”
Section: Thm Extracts Lessen Cell Growth/survival In Hnsccsmentioning
confidence: 99%